Methodology of situational management of critical infrastructure security - Michał Wiśniewski (Foundations of Management, 2020)
The article discusses the issues of the critical infrastructure security management from the perspective of entities responsible for its security and development of an integral model of critical infrastructure security, and shows the methodology of situational management of critical infrastructure safety. Proposed solutions are used for CI mapping, enabling the generation of adverse event scenarios, estimation of the risks dependent on the considered CI, and determination of decision problem, indicating a set of protection activities for elimination or reduction of the risk in the security threshold.
Keywords: H12; 650; crisis management; critical infrastructure; risk assessment; security threshold; adverse event scenario